Kasih Sejati: Memahami Misi Secara Teks, Konteks, dan Komunitas Berdasarkan Yohanes 17:18 Pada PTT/AK - Sensius Amon Karlau (Sekolah Tinggi Teologi Tenggarong, 2020)
The existence of God is in essence impossible to shift, but, in fact seems to experience a shift that appears in human efforts to respond to the mission call. Efforts to